2003
DOI: 10.1007/s00417-002-0591-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of experimental angiogenesis of cornea by somatostatin

Abstract: Our study demonstrated that SST 14 can reduce bFGF-induced corneal angiogenesis. This shows the potential value of somatostatin in the treatment of corneal neovascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 24 publications
0
18
0
3
Order By: Relevance
“…7 Recent studies have shown that angiogenesis inhibitors, such as endostatin, angiostatin, somatostatin, tissue inhibitor of metalloproteinase-3, peptide derived from thrombospondin-1, prolactin and brain-specific angiogenesis inhibitor 1 (BAI1), can inhibit corneal neovascularization and maintain corneal avascularity. [9][10][11][12][13][14][15][16] GA-binding protein (GABP) is a ubiquitously expressed nuclear transcription factor that is involved in a broad range of cellular processes and that regulates target gene expression in the cell cycle and cellular metabolism. 17 GABP is composed of two subunits: GABPa contains the erythroblast transformation-specific DNA-binding domain, whereas the substitutable subunit, GABPb or GABPg, contains ankyrin repeats and the transcriptional activation domain.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recent studies have shown that angiogenesis inhibitors, such as endostatin, angiostatin, somatostatin, tissue inhibitor of metalloproteinase-3, peptide derived from thrombospondin-1, prolactin and brain-specific angiogenesis inhibitor 1 (BAI1), can inhibit corneal neovascularization and maintain corneal avascularity. [9][10][11][12][13][14][15][16] GA-binding protein (GABP) is a ubiquitously expressed nuclear transcription factor that is involved in a broad range of cellular processes and that regulates target gene expression in the cell cycle and cellular metabolism. 17 GABP is composed of two subunits: GABPa contains the erythroblast transformation-specific DNA-binding domain, whereas the substitutable subunit, GABPb or GABPg, contains ankyrin repeats and the transcriptional activation domain.…”
Section: Introductionmentioning
confidence: 99%
“…These include medication, laser photocoagulation, and surgery. Several angiogenesis inhibitors have been identified and tried as medical treatment, including prolactin, 3 endostatin, 7 angiostatin, 8 somatostatin, 9 cyclosporin A, 18 TNP-470, 19 steroids, 20 nonsteroidal antiinflammatory drugs, 21 thalidomide, 22 methotrexate, 23 and culture supernatant of human amniotic cells. 24 Recently, targeted macrophage metalloelastase or angiostatin gene transfer has been tried to halt angiogenesis in a mouse tumor model, 25,26 and naked plasmids have been shown to be taken up by corneal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Recognition of the potential benefits of controlling angiogenesis has led to a search for angiogenesis inhibitors. 6 Several angiogenesis inhibitors have been identified, such as prolactin, 3 endostatin, 7 angiostatin, 8 somatostatin, 9 and peptide derived from thrombospondin-1 (TSP1), 10 although some of which are the fragments of larger proteins. However, there have been a few studies of gene delivery as a way to reduce neovascularization in the eye.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recent progress in the graphic editing software, automated methods have some limitations. First, the optimization and validation of any automated quantitative tool are questionable [36][37][38]. Second, it does not allow suicient appreciation of details on vessel extent, localization, leakage, origin, and diferentiation of the aferent and eferent systems.…”
Section: Paraclinical Evaluation Of Corneal Vascularizationmentioning
confidence: 99%